Variations in Site of Lithiation of N-[2-(4-Methoxyphenyl)ethyl]pivalamide – Use in Ring Substitution - Smith, Keith; El-Hiti, Gamal A.; Alshammari, Mohammed B. (Synlett, 2013)
Lithiation of N-[2-(4-methoxyphenyl)ethyl]pivalamide at –20 to 0 °C with three equivalents of n-BuLi in anhydrous THF, followed by reactions with various electrophiles, gives high yields of products involving ring substitution ortho to the pivaloylaminoethyl group, which was unexpected in view of earlier results reported with t-BuLi.
Keywords: N-[2-(4-methoxyphenyl)ethyl]pivalamide; directed lithiation; synthesis; electrophile; dilithium intermediate